Association of Dual Venous Anastomosis with Reduced Risks for Flap Congestion in Microsurgical Lower Extremity Reconstruction: A Multicenter Study - Lee, Sang-Hun; Lee, Kyeong-Tae; Park, Bo Young (Journal of Reconstructive Microsurgery, 2022)
Background Flap congestion related with venous thrombosis is a major cause for microsurgical lower extremity reconstruction failure. Conducting dual venous anastomosis has been suggested to reduce risks for the adverse outcomes; however, its efficacy remains controversial. This study evaluated a potential association of dual venous anastomosis with the development of flap congestion in diverse clinical situations.Methods This multicenter study included patients who underwent microsurgical lower extremity reconstruction at two institutions. They were divided into two groups based on the number of venous anastomoses—single and dual groups. Their perfusion-related complications (PRCs), including total/partial flap loss, arterial or venous insufficiency, and emergent reoperation, were compared. Independent association of the number of venous anastomoses with the outcomes was evaluated. Further analyses were conducted using propensity score matching.Results In total, 225 cases were analyzed, of which 92 were included in the single group and the other 133 in the dual group. The two groups had generally similar baseline characteristics. The dual group presented significantly lower rates of PRC, including total/partial flap loss, flap congestion, and emergent reoperation. Multivariable analyses showed that conducting dual venous anastomoses was associated with reduced risks for the development of overall PRC and flap congestion. These associations were more prominent when restricting analyses for cases with chronic wound and trauma (vs. oncologic defects). Similar associations were observed in the propensity score matching analysis.Conclusion Conducting dual venous anastomosis seems associated with reduced risks for flap congestion in microsurgical lower extremity reconstruction, especially for cases with unfavorable conditions.
Keywords: lower extremity reconstruction; dual venous anastomosis; congestion